The Relationship between Interpersonal Communication and Social Support of Students at STIKES Katolik St. Vincentius a Paulo Surabaya - Baswara Yua Kristama; Kurniawaty, Yuni; Winarni, Sri (Jurnal Spektrum Komunikasi, 2024)
The urgency of effective communication can build healthy and harmonious relationships between individuals, both in the formal sphere, such as between teachers and students, and in the informal sphere, such as between fellow students. This interpersonal communication will have an impact on social support, which begins with good interpersonal communication, becoming an important element in helping students overcome stress and improve their well-being. Objective: To analyze the relationship between interpersonal communication and social support for STIKES Katolik St. Vicnentius a Paulo Surabaya. Method This type of research is a quantitative correlation research with a cross-sectional design. Research location at the STIKES Katolik St. Vicnentius a Paulo Surabaya in December 2024. St. Vincentius in Paulo Catholic student population. Vincentius in Paulo Surabaya had 424 people with a sample size of 206 people, using simple random sampling. The measurement tools used were the social support questionnaire (Interpersonal Support Evaluation List/ISEL-40) and the interpersonal communication skills scale questionnaire. Using the Spearman Rank statistical test. The results of most interpersonal communication were in the average range of 74.8%. The social support of the respondents was in the average range of 70.4%. Spearman Rank statistical test p = 0.000 positive correlation coefficient 206, namely that there is a weak relationship between interpersonal communication and social support of students. The better the interpersonal skills, the greater the social support of the student. Educational institutions can create an environment conducive to effective interpersonal communication between students, both formal (students and teachers) and informal (among students), so that social support can also be well created in the educational environment.